Tamoxifen induces toxicity, causes autophagy, and partially reverses dexamethasone resistance in Jurkat T cells. Issue 5 (15th January 2019) - Torres-López, Liliana; Maycotte, Paola; Liñán-Rico, Andrómeda; Liñán-Rico, Liliana; Donis-Maturano, Luis; Delgado-Enciso, Iván; Meza-Robles, Carmen; Vásquez-Jiménez, Clemente; Hernández-Cruz, Arturo; Dobrovinskaya, Oxana
Abstract: Estrogens demonstrate biological activity in numerous organ systems, including the immune system, and exert their effects through estrogen receptors (ER) of two types: intracellular ERα and ERβ that activate transcriptional factors and membrane G protein-coupled ER GPER. The latter is capable to mediate fast activation of cytosolic signaling pathways, influencing transcriptional events in response to estrogens. Tamoxifen (TAM), widely used in chemotherapy of ERα-positive breast cancer, is considered as an ERα antagonist and GPER agonist. TAM was shown to possess "off-target" cytotoxicity, not related to ER in various tumor types. The present work was designed to study biological effects of TAM on the glucocorticoid (GC)-resistant cell line Jurkat, derived from acute lymphoblastic leukemia of T lineage (T-ALL). We have shown that T-ALL cell lines, in contrast to healthy T cells, express only GPER, but not ERα or ERβ. TAM compromised mitochondrial function and reduced the viability and proliferation of Jurkat cells. Additionally, TAM induced autophagy in a GPER-dependent manner. Gene expression profiling revealed the up-regulation of autophagy-related gene ATG5 . Interestingly, TAM sensitized Jurkat cells to dexamethasone (DEX) treatment, which may be related to its capacity to cause autophagy. We suggest that TAM-based adjuvant therapy may represent a novel strategy in T-ALL patients handling. Graphical Abstract: GPER-mediated TAM-induced autophagy sensitizes GC-resistant Jurkat cells to DEX.